2021
DOI: 10.3390/ijerph18052638
|View full text |Cite
|
Sign up to set email alerts
|

Statewide Ambulance Coverage of a Mixed Region of Urban, Rural and Frontier under Travel Time Catchment Areas

Abstract: This study examines the statewide service coverage of emergency medical services (EMS) in view of public health planners, policy makers, and ambulance service managers. The study investigates the statewide service coverage in a mixed region of urban, rural, and frontier regions to address the importance of ambulance service coverage at a large scale. The study incorporated statewide road networks for ambulance travel time, census blocks for population, and backup service coverage using geographic information s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…32 Despite this decline, there are substantial regional and rural‐urban differences in ECIT with a recent study reporting that ECIT in the MidWest urban and rural areas range from 2 to 5 minutes, and 4 to 6 minutes, respectively. 33 This study found that about two‐thirds of persons exposed to crashes had ECIT of 1 minute or less at all times of the day with the proportion slightly larger during the rush hour compared to the nonrush hour period. However, about half of the persons exposed to crashes in rural areas experienced ECIT longer than a minute compared to a third of those exposed to crashes in urban areas.…”
Section: Discussionmentioning
confidence: 70%
“…32 Despite this decline, there are substantial regional and rural‐urban differences in ECIT with a recent study reporting that ECIT in the MidWest urban and rural areas range from 2 to 5 minutes, and 4 to 6 minutes, respectively. 33 This study found that about two‐thirds of persons exposed to crashes had ECIT of 1 minute or less at all times of the day with the proportion slightly larger during the rush hour compared to the nonrush hour period. However, about half of the persons exposed to crashes in rural areas experienced ECIT longer than a minute compared to a third of those exposed to crashes in urban areas.…”
Section: Discussionmentioning
confidence: 70%
“…Possible measures could include relaxation of regulations on interstate and cross-border ambulance travel, increasing availability of emergency air transportation, speed regulations for emergency vehicles, geographical backup coverage, and reduced chute times (i.e., delays in EMS call dispatch and travel). 118 Improvements in emergency response systems may also be facilitated by capacity building in underserved areas, telemedicine systems, 119 and standards for establishing centers equipped to receive patients with acute DoC. 114 120 121 122 123 124 125 126…”
Section: Hyperacute Phasementioning
confidence: 99%
“…Possible measures could include relaxation of regulations on interstate and cross-border ambulance travel, increasing availability of emergency air transportation, speed regulations for emergency vehicles, geographical backup coverage, and reduced chute times (i.e., delays in EMS call dispatch and travel). 118 Improvements in emergency response systems may also be facilitated by capacity building in underserved areas, telemedicine systems, 119 and standards for establishing centers equipped to receive patients with acute DoC. 114,[120][121][122][123][124][125][126] Another area of ethical concern is ensuring that prehospital care and triage reflect patients' values and goals.…”
Section: Hyperacute Phasementioning
confidence: 99%
“…Expected response time defines the service coverage. The response time of the prehospital care EMS is a sum of chute time and travel time of total EMS mission time (Lee, McDonald, O'Neill, & Montgomery, 2021; Tansley et al., 2016; Ulteig, 2013). Chute time is an interval between the time an ambulance crew or first responders are notified and the ambulance is en route .…”
Section: Introductionmentioning
confidence: 99%
“…The case study carried out here was inspired by the ambulance service area map in North Dakota (State of North Dakota, 2009) and Lee et al. (2021). North Dakota is classified as a rural state, and the state maintains urban, rural, and frontier areas for prehospital services.…”
Section: Introductionmentioning
confidence: 99%